(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The paper discusses about circumstances, environment and benefits that compel digitization of academic libraries due to the advent of Information and Communication Technology (ICT).It also highlights its challenges for converting traditional library resources to digital format.